Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/j.pain.0000000000000810
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced delivery of IL-1 receptor antagonist to the central nervous system as a novel anti–transferrin receptor-IL-1RA fusion reverses neuropathic mechanical hypersensitivity

Abstract: Delivery of an interleukin-1 antagonist across the blood–brain barrier results in analgesia in the Seltzer model of neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 37 publications
1
75
0
Order By: Relevance
“…11,[14][15][16][17] Lowering their affinity facilitated their sorting into early endosomes, 18 improved their transcytosis and increased their levels in the brain parenchyma. 11,19 The comparisons of TfR engagement with bi>valent or monovalent TfR antibodies revealed that a monovalent format achieved improved transcytosis across the BBB, regardless of affinity, 12 whereas a high>affinity bi>valent antibody was destined to degradation in brain endothelial lysosomes. 12 A pH>sensitive bi>valent TfR antibody, with lower binding affinity at the acidic pH found in endocytic compartments, also demonstrated improved BBB transcytosis in vitro.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…11,[14][15][16][17] Lowering their affinity facilitated their sorting into early endosomes, 18 improved their transcytosis and increased their levels in the brain parenchyma. 11,19 The comparisons of TfR engagement with bi>valent or monovalent TfR antibodies revealed that a monovalent format achieved improved transcytosis across the BBB, regardless of affinity, 12 whereas a high>affinity bi>valent antibody was destined to degradation in brain endothelial lysosomes. 12 A pH>sensitive bi>valent TfR antibody, with lower binding affinity at the acidic pH found in endocytic compartments, also demonstrated improved BBB transcytosis in vitro.…”
mentioning
confidence: 99%
“…12 A pH>sensitive bi>valent TfR antibody, with lower binding affinity at the acidic pH found in endocytic compartments, also demonstrated improved BBB transcytosis in vitro. 13 Recent study also showed that the mouse anti>TfR antibody 8D3 bioengineered to reduce Kd 4 from 1.2 nM to 130 nM resulted in a 44>fold increase in total brain and spinal cord exposure 19 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…High affinity binding of antibodies to TfR1 appears to impede transcytosis by lysosomal targeting or preventing receptor dissociation consequently trapping the antibody inside the capillary endothelium [8,10,[36][37][38]. It was further shown that monovalent formatting or lowering the affinity of TfR1 antibodies could boost brain transport in vivo [8,[11][12][13]. Conversely, a series of biochemical, histological, biodistribution, pharmacokinetic and pharmacodynamic studies showed that neither high-affinity binding (0.6 nM KD) nor a bivalent configuration impeded BBB transport of TXB2-hFc via TfR1.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-TfR1 antibodies can accumulate in brain capillaries with limited release into the brain parenchyma [8] and can direct the receptor for lysosomal degradation [9,10]. These antibodies have been subsequently re-engineered to reduce their safety liabilities and improve brain penetration either by monovalent formatting or a reduction in TfR1 binding affinity [8,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%